2014
DOI: 10.1021/am5031962
|View full text |Cite
|
Sign up to set email alerts
|

Gracilaria lemaneiformis Polysaccharide as Integrin-Targeting Surface Decorator of Selenium Nanoparticles to Achieve Enhanced Anticancer Efficacy

Abstract: The poor permeability of glioma parenchyma represents a major limit for antiglioblastoma drug delivery. Gracilaria lemaneiformis polysaccharide (GLP), which has a high binding affinity to αvβ3 integrin overexpressed in glioma cells, was employed in the present study to functionalize selenium nanoparticles (SeNPs) to achieve antiglioblastoma efficacy. GLP-SeNPs showed satisfactory size distribution, high stability, and selectivity between cancer and normal cells. In U87 glioma cell membrane, which has a high in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 141 publications
(81 citation statements)
references
References 49 publications
1
76
0
Order By: Relevance
“…[20][21][22] SeNPs can be employed in nanocarriers for drug delivery and therapeutic agents due to their excellent bioavailability, low toxicity and significant radiosensitization effects with X-ray irradiation. [23][24][25] Selenadiazole derivatives and Se-containing Ru complexes have been designed to combine radiotherapy and chemotherapy in vitro and in vivo due to their surface plasmon resonance effect and high refractive index, which facilitate light absorption. [26][27][28] As new responsive materials for use in combination radiotherapy and chemotherapy, diselenide-containing polymers have proven to be more sensitive to a low dose of γ-radiation than similar disulfides because the bond energy of Se-Se (172 kJ mol − 1 ) is weaker than that of the S-S bond (240 kJ mol − 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] SeNPs can be employed in nanocarriers for drug delivery and therapeutic agents due to their excellent bioavailability, low toxicity and significant radiosensitization effects with X-ray irradiation. [23][24][25] Selenadiazole derivatives and Se-containing Ru complexes have been designed to combine radiotherapy and chemotherapy in vitro and in vivo due to their surface plasmon resonance effect and high refractive index, which facilitate light absorption. [26][27][28] As new responsive materials for use in combination radiotherapy and chemotherapy, diselenide-containing polymers have proven to be more sensitive to a low dose of γ-radiation than similar disulfides because the bond energy of Se-Se (172 kJ mol − 1 ) is weaker than that of the S-S bond (240 kJ mol − 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…As described in our previous paper, 18 the Beckman flow cytometry was used to analyze the cell cycle distribution.…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
“…17 Drug delivery systems with a pH response have been widely used, because they can swell and shrink in different pH condition so as to achieve targeted drug delivery and efficient drug release in cancer cells. 18,19 The Arg-Gly-Asp (RGD) peptide, an excellent targeting reagent, can recognize the integrin receptor which is overexpressed in a lot of human tumor cells and is able to bind to both tumor cells and endothelial cells. 20 Therefore, this pH-responsive nanosystem was also decorated with RGD peptide to achieve targeted drug delivery.…”
mentioning
confidence: 99%
“…24 Liu et al 25 reported the use of SeNPs as carriers of 5-fluorouracil to enhance anticancer efficacy. SeNPs' conjugation of transferrin could increase their anticancer activity as reported by Huang et al 26 SeNPs functionalized with polyethylene glycol were designed to overcome drug resistance in hepatocellular carcinoma HepG2 cells by Zheng et al 27 SeNPs were used with surface decoration by Gracilaria lemaneiformis polysaccharide to achieve enhanced anticancer efficacy by Jiang et al 28 SeNPs are superior because they are degradable in vivo and can be used as nutrients for many kinds of normal cells or as antiproliferative agents for many kinds of cancer cells. 29 Functionalized SeNPs could be internalized by cancer cells through endocytosis, which induces apoptotic cell death by triggering mitochondria-mediated apoptosis pathways.…”
Section: Introductionmentioning
confidence: 96%